La Facoltà di Architettura di Firenze fra tradizione e cambiamento Atti del convegno di studi (Firenze, 29-30 Aprile 2004) - Gabriele Corsani (Firenze University Press, 2007)
The volume comprises the proceedings of the study days in the Faculty of Architecture (29-30 April 2004) broken down into four thematic sections: The original characteristics of the Florentine school, From Higher School to Faculty, the Florentine school and the contributions from outside, Contemporary metamorphoses. The contributions focus the phases of formation and evolution of the Higher School (1926) and later Faculty (1936) of Architecture, underlining the most significant passages, starting from the initial consolidation of the didactic structure and the emergence of a "Florentine school" characterised by the two strands traceable to Raffaello Fanoni and Giovanni Michelucci. A parallel experience is provided by the contribution of the external teachers, in particular of the Roman school, with lively and at times conflicting approaches. The present situation, albeit with the necessary disciplinary dialectic, features a settlement of the divergences around themes of the relations between architecture, environment and landscape.